Тройные диаграммы систем Cu-Pd-Me (Me=Au, Ag, Ni, Pt); Перспективные материалы в технике и строительстве (ПМТС-2013) - Морозов М. М. Максим Михайлович; Маркова Т. Н. Татьяна Николаевна; Клопотов В. Д. Владимир Дмитриевич; Потекаев А. И. Александр Иванович; Кнестяпин Е. А. Евгений Александрович (2013, 2013)
Заглавие с экрана